TYPOLOGICAL STUDY OF THE PHONETIC LEVEL OF THE RUSSIAN AND UZBEK LANGUAGES - Umarova M.S.; Shakhobiddinova D.S. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: The article is devoted to a comparative-typological study of the phonetics of the modern Russian and Uzbek languages.